Scleroderma venenatum sp. nov., S. venenatum var. macrosporum var. nov. and S. suthepense new to China - Zhang, Yi-Zhe; Sun, Cheng-Ye; Sun, Jian; Zhang, Kai-Ping; Zhang, Hong-Shun; Guo, Xiang; Zhou, Ya-Juan; Zheng, De-Sheng; Li, Hai-Jiao (Phytotaxa, 2020)
Taxonomic and phylogenetic studies on Scleroderma in China were carried out. One poisonous species was discovered at the scene of poisoning that could not match any known species, and is described morphologically and molecularly as a new species: Scleroderma venenatum. It is characterized by its two layered peridium, brown to greyish brown surface with scattered, small and thin scales, presence of moniliform hyphae in gleba and middle size echinulate basidiospores (9−13 μm, including ornamentation) with dense narrow pyramidal warts. At the same time, S. venenatum var. macrosporum was found which shares most characteristics with S. venenatum var. venenatum except its distinctly larger basidiospores (12−16 μm), and occasionally presence of clamp connections in the inner layer of the peridium. Scleroderma suthepense, originally described from Thailand was also discovered from tropical areas of Guangdong and Yunnan Provinces, which was characterized by its strongly reticulate basidiospores (8−11.5 μm). A key to the known species of Scleroderma in China is also provided.